Discovering Islam - David M. Hart (International Institute of Islamic Thought, 1988)
This book, written by Akbar Ahmed, is particularly apt and to the point. The book’s title and subtitle seem, to this reviewer at least, an accurate reflection of its content: it has an introduction also called “Discovering Islam”, then two major sections (each divided into chapters of unequal length; the first and longer on ”The Pattern of Muslim History” and the second on ”Contempomy Muslim Society” (with a conclusion again entitled “Discovering Islam”). As Ahmed states at the outset, he writes as a committed participant in, as well as an observer of, Islam, and furthermore, he makes no bones about his “South Asian” (read ”Pakistani“) perspective and bias with respect to Islam as a whole. Ahmed has already observed in some of his earlier work, that there is only one Islam, not many “islams” (contrary to the views asserted recently by a number of non-Muslim students of the subject); and this is so despite the wide range and disparity of Muslim societies around the globe. Neither of these arguments is original with its present proponents. Ahmed puts forward both his view of the Islamic ideal, as well as the way some Muslims order their lives with respect to this ideal, with surprising force and vigor. He states, “Economic, political and ethnic-social, cultural pressures act to compromise notions of the ideal, thereby creating ambiguity around it. The demarcation of Muslim societies is therefore not division between white ideal and black non-ideal, but an ongoing relationship between the two marked by areas of grey. Taken together the arguments will assist us in our search for . . . an Islamic world-view of society and history” (p. 5). A further very telling quote which reveals the book to be neither an apology for, nor an attack on, the West (of which its author is admittedly and justifiably critical), but a clear statement: ”While the twentieth century cannot reject Islam-it is here to stay as a force; in turn, Islam must accept the twentieth century. It will not go away, and rejection is the easy way out. Islam must come to terms with the twentieth century; by doing so it will come to terms with itself‘ (p. 8). In the first section of the book we are taken on a tour of Islamic history. It is of necessity selective, but both the wide-angle lens shots, as well as ...